The impact of celebrity endorsement on millennials’ purchase intention towards local health and beauty product / Zarith Delaila Abd Aziz, Muhammad Khalil Omar and Shahira Ariffin - Abd Aziz, Zarith Delaila; Omar, Muhammad Khalil; Ariffin, Shahira (Faculty of Business and Management UiTM Shah Alam, 2020)
The growth in the local beauty and health products in Malaysia have surged rapidly, so does the trend in using celebrity endorsements making this study is crucial to help determine its success due to the large investment involved. Therefore, the objective of this study is to examines the extent at which millennials has been impacted by celebrity endorsement on their purchase intention for local health and beauty products. Quantitative method has been used and 313 data were collected among millennials in Selangor, Malaysia. The result of the study revealed that celebrity attractiveness has a high impact on respondents in developing their purchase intention for local and health beauty products. Meanwhile celebrity credibility shows the moderate impact on millennials. The result of this study offer valuable insight for marketing practitioner in regards to the use of celebrity as endorsers that may or may not trigger millennial’s in the product use.